CPSF1 inhibition promotes widespread use of intergenic polyadenylation sites and impairs glycolysis in prostate cancer cells - Kiel T. Tietz; Braedan M. McCluskey; Conor R. Miller; Yingming Li; Sarah A. Munro; Scott M. Dehm (Cell Reports)
Summary: Localized prostate cancer can be cured by radiation or surgery, but advanced prostate cancer continues to be a clinical challenge. Altered alternative polyadenylation occurs in numerous cancers and can downregulate tumor-suppressor genes and upregulate oncogenes. We found that the cleavage and polyadenylation specificity factor (CPSF) complex factor CPSF1 is upregulated in patients with advanced prostate cancer, with high CPSF1 expression correlating with worse progression-free survival. Knockdown of CPSF1 selectively inhibited the growth of prostate cancer cells and reduced glycolytic output. Evaluating the changes in global poly(A) site usage in prostate cancer cells following CPSF1 knockdown revealed widespread usage of intergenic poly(A) sites distal to annotated 3′ UTRs, which lengthened 3′ UTRs and decreased levels of thousands of mRNAs, including key glycolysis genes. These findings uncover a role for CPSF1 in the suppression of intergenic poly(A) sites in prostate cancer and nominate CPSF1 as a therapeutic target in advanced prostate cancer.